Quiz (1 point)
- (list x and xs) multiplied by (list y and (list y2 and ys)) = sum of unsigned integers (list x and xs) and ((list x and xs) multiplied by (decrement (list y and (list y2 and ys)) by 1))
- decrement (list 0 and (list 1 and (empty list))) by 1 = list 1 and (empty list)
- (list x and xs) multiplied by (list 1 and (empty list)) = list x and xs
if decrement (list 0 and (list 1 and (empty list))) by 1 = list 1 and (empty list), then (list x and xs) multiplied by (decrement (list 0 and (list 1 and (empty list))) by 1) = (list x and xs) multiplied by (list 1 and (empty list))
if (list x and xs) multiplied by (decrement (list 0 and (list 1 and (empty list))) by 1) = (list x and xs) multiplied by (list 1 and (empty list)), then sum of unsigned integers (list x and xs) and ((list x and xs) multiplied by (decrement (list 0 and (list 1 and (empty list))) by 1)) = sum of unsigned integers (list x and xs) and ((list x and xs) multiplied by (list 1 and (empty list)))
if (list x and xs) multiplied by (list 1 and (empty list)) = list x and xs, then sum of unsigned integers (list x and xs) and ((list x and xs) multiplied by (list 1 and (empty list))) = sum of unsigned integers (list x and xs) and (list x and xs)
if the following are true:
- a = b
- b = c
then a = c
if the following are true:
- a = b
- b = c
then a = c
Please write your proof in the table below. Each row should contain one claim. The last claim is the statement that you are trying to prove.